Towards sustainable solutions: Comprehensive review of advanced porous materials for CO₂ capture, hydrogen generation, pollutant degradation, and energy application - Iltaf Khan; Anam Altaf; Samreen Sadiq; Shoaib Khan; Aftab Khan; Sohail Khan; Muhammad Humayun; Abbas Khan; Rasha A. Abumousa; Mohamed Bououdina (Chemical Engineering Journal Advances)
Recently, there have been significant developments in advanced porous materials, especially with types like porous organic polymers, metal-organic frameworks, hydrogen-bonded organic frameworks, covalent organic frameworks, zeolites, and porous aromatic frameworks. These materials are gaining attention for their remarkable characteristics, including high surface area, adjustable pore sizes, strong adsorption capacity, stability under various conditions, effective catalytic properties, and good electrical conductivity, making them useful across a range of applications. This review article highlights the various types, structures, and synthesis methods of POPs, MOFs, HOFs, COFs, zeolites, and PAFs, in addition to their important applications such as hydrogen generation, gas sensing, CO2 conversion, pollutant degradation, CO2 capture, hydrogen evolution/oxygen evolution reactions, and batteries. Lastly, the future perspective of APMs along with the necessary steps to be taken and embraced in order to make them usable for long-term and large-scale applications will help in opening new innovative gateways to the research field.